Critical Analysis of Physiotherapy Techniques in Chronic Pain Management: Improving Quality of Life - Al fadhil, Mansour Hamad Ali; Al-alhareth, Hadi Saeed Hadi; Alismail, Mohammed Hussain Mohammed; ALyami, Yahya Ali Saleh; Alyami, Khalid Ali Hadi; Al zamanan, Ameen Saleh Ali (Journal of Ecohumanism, 2024)
Chronic pain is nowadays one of the most frequent disorders affecting the quality of life and presenting difficulties to the population and the healthcare systems all over the world. Amongst the set of physiotherapy management tools, manual therapy, therapeutic exercises, and technologies are prominent in the treatment of chronic pain. The objective of this paper is to critically evaluate the successfulness of utilizing physiotherapy in managing chronic pain as well as improving the patient’s quality of life. Using this approach, based on recent research, it discusses and analyzes various forms of treatment, such as manual therapies, exercise-based approaches, and various other technologies, with a focus on outcomes and relevancies. This work underscores the importance of patient-centered care and an interdisciplinary approach in future approaches to chronic pain.